The Green and Lean Dairy Supply Chain Model: The case of a Libyan Dairy Company - BADI, MESBAH SALEH (2015)
Lean management was first implemented by Toyota in the automobile industry and has attracted the attention of many companies worldwide from various industries and sectors due to cost pressures and resource scarcity issues. Moreover, contemporary human activities have caused concern regarding its negative effects on the environment. Therefore, global agreements such as the Kyoto protocol were initiated to force companies to adopt green production and eliminate green wastes. The adoption of lean to cut wastes for cost reasons and then to separately adopt green, to cut wastes for legal and environmental reasons was questioned by researchers who believe that lean and green should be adopted simultaneously to maximise the benefits. Although, lean and green are targeting similar types of wastes, there are several contradictions related mainly to the Just In Time (JIT) tool which could decrease lean wastes but increase green wastes. The developed frameworks focus on maximising similarities and minimizing conflicts.